Replacement of Line Loads acting on slabs to equivalent uniformly Distributed Loads (Journal of Engineering, 2012)
This study aims to derive a general relation between line loads that acting on two-way slab system and the equivalent uniformly distributed loads. This relation will be so useful to structural designer that are used to working with a uniformly distributed load and enable them to use the traditional methods for analysis of two-way systems (e.g. Direct Design Method). Two types of slab systems, Slab System with Beams and Flat Slab Systems, have been considered in this study to include the effect of aspect ratio and type of slab on the proposed relation. Five aspect ratios, l2/l1 of 0.5, 0.75, 1.0, 1.5 and 2.0, have been considered for both types of two-way systems. All necessary finite element analyses have been executed with SAFE Software. Data obtained from the F. E. analyses have been used in a statistical analysis using Statistic Software to derive the relation based on a Linear Regression Analysis.